A Novel Concept for Dynamic Network Reduction Dedicated to Real-Time Application - Kuri, Ananya; Gäbel, Sebastian; Burlakin, Ilya; Wagner, Timo; Mehlmann, Gert; Luther, Matthias (Kyoto Symposium 2022 - CIGRE Japan, 2022)
An increasing power electronic based generation and distribution causes new requirements for the power system. It pushes the limits of hardware and software resources for modelling and simulation while demanding more accuracy, with modern methods for analysis [1]. Therefore, stakeholders increasingly insist on analyzing the new source’s interactions and impacts on the power grid under offline and real-time environments. In power system engineering, real-time simulators form the interface between the virtual and real-world and assess electrical equipment and control. Thus, they serve as a tool for digital twins. The simulation of dynamic phenomena requires a plausible network model with the device under test to assess those interactions accurately. This is achieved by a suitable dynamic reduction of the grid areas to be investigated, with complex reduction process requirements. Historically the main reason for dynamic network equivalents was the limited CPU capacity enabling steady-state and dynamic calculations on extended networks. The results often had a reasonable degree of approximation. Modern computers are equipped with performant multi-core CPUs and large RAM, yet dynamic network equivalents of extended grids are still used nowadays. One of the main reasons for developing model equivalents is to accurately reproduce and simulate complex inverter-based equipment and depict its interaction with the network in software tools and real-time simulators. Due to the control structure, among other things, integration time steps are often chosen in the microsecond range. Hence, such simulations usually take ample time and require high processing power. This is a usual concern when equipment test matrices with several hundred cases have to be dealt with. Simulating a network and the device under test in a real-time environment has additional challenges. Several approaches and tools to achieve reduced networks are available; however, none of the approaches are customized to achieve reduced models for real-time simulators. The paper highlights a dynamic model reduction methodology that accommodates real-time requirements. The methodology concentrates on achieving a high degree of reduced grid elements focusing on the real-time simulator requirements and developing an interactive user automation process. The dynamic reduction process is based on a hybrid methodology of machine coherency and estimation-based equivalent methods achieved via Multi-Objective Genetic Algorithm NSGA-II presented in [2]. The paper focuses on the next phase of transferring the equivalent developed in an offline environment to the real-time environment considering the hardware requirements and automating the process. The reduced model of the targeted network area consists of a physically realistic grid model rather than a mere mathematical equivalent and is therefore suited for real-time simulations with hardware-in-the-loop (HIL). The complete path and endeavor from developing offline equivalents to emulating the complete system on real-time hardware is the prime focus of the paper.<br

A novel Grid Forming Control Scheme revealing a True Inertia Principle - Kuri, Ananya; Zurowski, Rainer; Mehlmann, Gert; Audring, Dirk; Luther, Matthias (IEEE Transactions on Power Systems, 2021)
This paper proposes an unconventional strategy for a grid forming converter, based on a phase restoring control concept by which a constant steady state frequency is achieved. This control scheme is inherently without a phase-locked loop (PLL) and keeps the power system frequency at its nominal value. Under disturbance, the control response mimics infinite virtual inertia since the power system frequency always returns to its nominal value. Therefore, this control presents a physical equivalence to a power system response with substantial inertia provided by synchronous machines. The understanding of frequency drift as a local phenomenon and power system frequency as a global aspect is briefly introduced. Further, the inherent discretization of a converter control as part of the feedback loop over the continuous network system is also considered. The concept has been mathematically investigated in a realistic test bench and global stability of the control is displayed based on the necessary boundary conditions. Simulation results supporting the mathematical hypothesis and visualizing the controller actions are presented. As a beneficial coincidence of these ideas, the control structure ensures similar responses in both electromagnetic transients (EMT) and root mean square (RMS) simulations.<br
Keywords: Grid-forming converters; EMT and RMS models; phase restoring control; true virtual inertia; power system stability; global stability; converter operated systems

Challenges for Integration of Renewable Energy in Public Grid - Kuri, Ananya; Brackenhammer, Eckart (Wind and Solar Integration workshop 2022, 2022)
Integrating renewable energy is one of the current and future subjects for the energy transition to CO2-neutral energy generation. New requirements, including grid and converter perspectives, must be considered as renewable power generation is carried out with power electronic converters. Inverter-based resources (IBRs) must meet grid connection regulations, forecasting options, time scheduling, storage options, and voltage quality. In this article, some essential requirements from the manufacturing perspective are described, and their testing procedure is displayed with the validation of simulation models. This paper further highlights the SICAM Power Plant Controller (PPC) for photovoltaic plants, enabling the plant operator to create generation forecasts for the next 2-3 days of power and energy. To be grid-code compliant, the PPC includes several functions to meet requirements, and its start-up sequence is also described. The system operator gains a grid-compliant model validated against site measurements. The procedures have been successfully applied to several IBR projects. Previews of new concepts to reach the future demands of integrating IBRs into the public grid are presented. Possible impacts on the power generation and components are assessed, and necessary countermeasures are applied with the influence and feasible solution for energy trading with IBRs. Future aspects of supra-harmonics and their impacts on public grids are described and presented as an outlook. This paper highlights the challenges of integrating IBRs and lessons learned based on project executions.<br

Comparison of Phase Restoring Principle with other Grid-Forming Methodologies - Kuri, Ananya; Raab, Alexander; Takhtaganov, Artur; Mehlmann, Gert; Luther, Matthias (IEEE Power and Energy Society General Meeting, 2023)
To tackle future power system challenges, the concept of grid-forming (GFM) inverter technology has emerged. Several GFM concepts are under research and display their characteristic behavior to meet the system's needs. An emerging concept called the 'Phase Restoring Principle' (PRP) with its active power control extension is described in this work. This non-linear control concept displays equivalent behavior to a slack (in frequency only), providing an ideal response to the power system under disturbance and avoiding the runaway effects produced by a phase-locked loop. Well-known Droop and Virtual Synchronous Machine (VSM)- based GFM schemes are considered for comparison. Each control methodology is implemented in the IEEE 9-bus test system in the electromagnetic transient domain to highlight their characteristics response in a network with a high proliferation of renewables. Each control approach provides inertia support and ensures stability under disturbance. The similarities between Droop- and VSM-based controls are witnessed. With its reduced order, PRP displays its key feature of prioritizing response to disturbance over set point changes and returning the system to nominal frequency with tuned parameters.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Grid-forming control; Phase Restoring Principle; power system stability

Concept and Operation of a distributed multi-domain Power System Laboratory with HiL-capabilities - Mehlmann, Gert; Scheibe, Christian; Resch, Simon; Kordowich, Georg; Richter, Julian; Wagner, Timo; Kuri, Ananya; Richter, Michael; Jäger, Johann; Luther, Matthias (ETG-Fachbericht 170: ETG Kongress 2023, 2023)

Converter Modelling Aspects at the Boundary between EMT and RMS Domain - Kuri, Ananya; Zurowski, Rainer; Mehlmann, Gert; Luther, Matthias (2022 International Conference on Smart Energy Systems and Technologies (SEST), 2022)
The main distinction between Electromagnetic Transients (EMT) and Root Mean Square (RMS) simulation is the constant power system frequency assumption in the RMS domain. This paper highlights the insufficiencies of RMS simulation in a converter-dominated power system traced back to an elementary mathematical model. A new variable called ‘Transient Voltage Difference’ is introduced to quantify the modeling error of inductively coupled converters in RMS domain with respect to EMT domain. The proposed index is calculated analytically and verified simulatively in a basic inductive network highlighting the coupling impedance effects. This quantity measures the transient output voltage capacity and is vital in Voltage Source Converter (VSC) design and planning studies. ‘Transient Voltage Difference’ emphasizes the hidden assumption on the converter’s output voltage rating, as current sources consider only the limitation in current. It can be used to assess the viability of the RMS domain modelling approach. This work highlights the basic design requirements for typical VSC in stability analysis.<br

Demonstration of Grid-Forming Controls in Hybrid AC/DC Grid in a Real-Time PHiL Environment - Richter, Michael; Kuri, Ananya; Richter, Julian; Wagner, Timo; Henninger, Stefan; Mehlmann, Gert (Electronics, 2025)
The transition to inverter-dominated power systems with novel control strategies has created weak grid scenarios, prompting extensive research into grid-forming (GFM) converters and advanced GFM control schemes. This study evaluates two GFM control strategies for their stabilizing effects in weakly interconnected and islanded power systems: the established Virtual Synchronous Machine (VSM) control and the newly developed Phase-Restoring Principle (PRP). The evaluation is conducted using a real-time electromagnetic transient (EMT) simulation testbed with Hardware-in-the-Loop (HiL) capabilities. The system includes a multi-terminal medium-voltage (MVDC) and high-voltage direct current (HVDC) network weakly coupled to a network equivalent, represented by a scaled synchronous machine (SynM) to replicate grid inertia. Modular multilevel converters (MMCs) model the converters, while Power Hardware-in-the-Loop (PHiL) experiments integrate real power hardware. Dynamic interactions, including islanded conditions, are emulated to assess the performance of GFM controls and their interactions in HV/MV and AC/DC systems. The results demonstrate the compatibility of diverse GFM schemes with grid-following controls and synchronous machines, emphasizing their positive contributions to system stability. This modular demonstrator, as a realistic prototype of future power systems, provides a flexible platform for testing emerging GFM strategies and hardware, supporting the development of robust and stable inverter-based grids.
CRIS-Team Scopus Importer:2025-03-14
Keywords: grid-following; grid-forming; HVDC; islanding; microgrid laboratory; MMC; MVDC multi-terminal; phase-restoring principle; PHiL; real time; virtual synchronous machine

Dynamic Modelling of Transmission Systems Based on Primary Energy Sources - Burlakin, Ilya; Porst, Johannis; Scheiner, Elisabeth; Kuri, Ananya; Mehlmann, Gert; Kühnapfel, Uwe; Luther, Matthias (Conference on Sustainable Energy Supply and Energy Storage Systems, 2022)

Dynamic model reduction based on coherency and genetic optimization methodology - Kuri, Ananya; Zhou, Xiaoyu; Mehlmann, Gert; La Seta, Piergiovanni; Luther, Matthias (ETG-Kongress 2021 - Von Komponenten bis zum Gesamtsystem für die Energiewende, 2021)
With the progressing integration of renewable energy sources, stakeholders are increasingly pushing for analyzing the interactions and impacts on the power grid, not solely based on software simulations. The device under test for integration into the grid may be simulated both in an offline and in real-time environment to investigate all possible dynamic interactions. This paper presents a dynamic model reduction methodology customized to accommodate the requirements for real-time (online) and non-real time (offline) analysis. The methodology concentrates on achieving a high degree of reduction, conserving the system behavior at the relevant nodes as precise as possible, and developing an interactive user automation process. The reduction process stems from a hybrid methodology of machine coherency and boundary equivalence achieved via Multi Objective Genetic Algorithm-NSGA-II. Additionally, the determination and parameterization of the equivalent generators’ controllers are also incorporated in the tooling. The reduced target network is a physical model and therefore suited for online simulations with Hardware-in-the-loop (HIL).<br

Interfacing real-time and offline power system simulation tools using UDP or FPGA systems - Scheibe, Christian; Kuri, Ananya; Feng, Yuyao; Zhao, Le; Xiong, Xuejun; La Seta, Piergiovanni; Liang, Xiao Peng; Knödtel, Johannes; Holzinger, Philipp; Reichenbach, Marc; Mehlmann, Gert (Electric Power Systems Research, 2022)
This contribution proposes a coupling interface between the real-time simulation system RTDS Novacor and the Power System Simulation Software PSS/E for electromagnetic transient (EMT) and phasor (RMS) hybrid simulations to enable a performant connection between the domains. For the coupling interface, two implementations with different characteristics in latency and hardware requirements are presented. Firstly, an Ethernet (UDP) based connection and secondly a fiber-based connection using the Aurora protocol. The first approach is purely software based, while the second one requires additional hardware. The technical implementation of the interfaces is explained in detail. The functionality of the interfaces is verified on the basis of an EMT-RMS simulation in a small overhead line test system.
CRIS-Team WoS Importer:2022-10-14

Modelling and challenges of integration of large renewable power plants - Kuri, Ananya; Audring, Dirk (2021 56th International Universities Power Engineering Conference (UPEC), 2021)
The connection of new large renewable power plants has challenges for optimal integration into a power system. Proper assessment is essential to consider any possible impact, apply countermeasures, and optimize performance. Early cooperation with the transmission system operator is required to align grid operation, plant operation, and specialists' experience from the manufacturer. The transmission system operator needs to gain an accurate steady-state and dynamic model of the converter-based power plant and confirmation that the plant configuration complies with grid codes. The investigations allow the manufacturer to modify or optimize the controllers, assess the impact on the shaft and other components, and perform corrections in protection devices and relay settings. This ensures given performance guarantees and proper operation of the newly commissioned plant. Any possible impact on the power system or the converter interfaced generation (CIG) is assessed, and necessary countermeasures can be applied. The described procedure was successfully applied at several renewable power plant projects of different types, such as hydropower plants, Wind and PV parks, providing communities and countries with efficient and renewable electrical power. The dynamic models developed are optimized, improved, and validated.<br

Modular Controller Design applied to Network Reduction Suited for Offline and Online Simulation - Kuri, Ananya; Sukumaran, Moraish; Mehlmann, Gert; Luther, Matthias (2021 56th International Universities Power Engineering Conference (UPEC), 2021)
The integration of renewables has caused dynamic network reduction to gain grounds in both offline and online applications. This paper proposes a new multifunctional and modular automatic voltage regulator (AVR) and governor (GOV) model that may be used as equivalent controllers for any reduced-order power system model. The idea stemmed from the structure preservation technique and applied to mathematical models. The simplified exciter system (SEXS) and the TGOV1 (GovSteam0) were used as base models. Modifications were made to their control structure to enable the emulation of a wide range of controller responses. The control development and parameter optimization of the new modular simplified AVR (MSimAVR) and the modular simplified GOV (MSimGOV) were performed in DIgSILENT PowerFactory using particle swarm optimization (PSO), respectively. Validation of the MSimAVR and MSimGOV responses was performed by benchmarking them against other standard controller types and displayed encouraging results. The newly developed controllers were implemented, optimized, and tested on a coherency-based dynamic reduced model of the New England 68-bus test network for the intended usage. Additionally, the new controllers also demonstrated good robustness and versatility when tested in the reduced network under different fault scenarios.<br

Performance of synchronizing units under reduced system strength - Kuri, Ananya; Höse, Richard; Mehlmann, Gert; Zurowski, Rainer; Audring, Dirk; Luther, Matthias (2021 IEEE PES Innovative Smart Grid Technologies Europe (ISGT Europe), 2021)
In today’s power systems, different trends can be observed, which reduce the total system strength. The result is a weakened reference voltage at the terminals of inverter-based generation. Present-day control systems have been designed under the assumption of a stiff reference voltage. Due to the reduced stiffness, it imposes a challenge for the inverters’ synchronization units. Without a precise synchronization, the entire converter control will become unstable. Therefore, advanced synchronization units are necessary. The performance of selected synchronization units, i.e., the phase locked loop (PLL) and frequency-locked loop (FLL), is analyzed under weak grid conditions. When utilizing the PLL, additional filtering is beneficial to extract the positive-sequence voltage vector. In general, the FLL turns out to be a more robust solution. Furthermore, the dependence of the voltage at the coupling node on the converter and the grid impedance is investigated analytically. In the case of weak grids, the influence of the load on the node voltage must be considered. Thus, a novel impedance ratio is introduced to assess the system strength under weak grid conditions. <br
Keywords: FLL; PLL; SCR; Synchronization; System strength; Weak grids

Phase Restoring Principle: Concept of a novel grid-forming converter scheme - Kuri, Ananya; Zurowski, Rainer; Mehlmann, Gert; Audring, Dirk; Luther, Matthias (ETG-VDE, Netzreglung und Systemführung 2022, 2022)
This paper presents a recently introduced globally stable grid-forming control scheme called the ‘Phase Restoring Prin-ciple’ (PRP) based on the change of perspective from the converter to the grid. The usual approach uses a synchronization method, such as a phase-locked loop (PLL) or frequency-locked loop (FLL), which serves as a reference frame for the design of the control behaviour and therefore designed to respond to set point changes. The Phase Restoring Principle utilizes a novel angular transformation of the reference frame in the opposite direction to a disturbance in the ohmic-inductive network. As a result, the control scheme prioritizes response to perturbation rather than setpoints. Thus, the PRP transformation directly takes over the main part of the control task of responding to an event, reduces the order of control dynamics, and serves as a basic block of the grid-forming control scheme. The main characteristics of PRP as a key element are discussed in the context of typical voltage-sourced models in a benchmarked test network. The dynamics are compared and discussed, visualizing the true virtual inertia characteristic inherent to PRP.<br

Power Dispatch Capacity of a Grid-Forming Control Based on Phase Restoring Principle - Kuri, Ananya; Zurowski, Rainer; Mehlmann, Gert; Luther, Matthias (Ieee Systems Journal, 2022)
The concept of grid-forming control is driving system operators to define this technology's capabilities and requirements to maintain grid stability, reliability, and the need to provide some of the services previously provided by synchronous generators. The novel control strategy, called the “Phase Restoring Principle” (PRP), was recently introduced for converter operated power systems. This article provides further insights and confirmation of the PRP grid-forming capabilities based on the response requirements from the perspective of the power system. It describes the extension of the control by supplementing PRP with active power control allowing the control to cooperate with other sources. The generalized small-signal solution of the control is derived and evidenced. Analytical deductions supported by simulative evidence of the power dispatch based on PRP are displayed in single, double, and triple converter configurations. The development of steady-state operating point and, hence, drift frequency using the principle of PRP with active power control is examined and discussed based on reference values and weighted gain selection. The enhanced PRP control structure also displays controller stability for sufficiently small drift frequencies and achieves nominal frequency with dedicated parameters.<br
Keywords: Controller stability; grid-forming converters; phase restoring principle; power dispatch capacity

Real Time Co-Simulation of Electromechanical and Electromagnetic Power System Models - Scheibe, Christian; Kuri, Ananya; Graf, Lorenz; Venugopal, Ravinder; Mehlmann, Gert (SEST 2022 - 5th International Conference on Smart Energy Systems and Technologies, 2022)
The goal of the paper is to demonstrate the feasibility of a real-time co-simulation of electromechanical /root-mean-square (RMS) and electromagnetic transient (EMT) power system models. For this purpose, a co-simulation framework has been developed along with a benchmark system for establishing boundary conditions for RMS-EMT modeling and co-simulation. For the co-simulation, a real-time machine of OPAL-RT has been coupled with another real-time simulator from the manufacturer RTDS Technologies Inc. The OPAL-RT simulator operates in RMS and EMT modes, whilst the RTDS simulator runs in EMT. An optimized low-latency high-speed optical fiber interface is developed to realize the co-simulation of the two modes across the two platforms. The Nordic Test System is used as an exemplary test network to create one part of the co-simulated network. Insights into modeling of discrete-continuous power systems are described and boundary conditions established to ensure accurate modeling for the different timescales and domains. Numerical results from a real-time co-simulation of a high-voltage direct current (HVDC) link running in EMT mode on the RTDS coupled with a model of the Nordic 32 Test System in RMS mode on the OPAL-RT simulator under fault conditions are presented.
CRIS-Team Scopus Importer:2022-11-11
Keywords: Co-simulation; EMT; Nordic32; real-time simulation; RMS